Teacher’s Verbal and Non-verbal Language in Teaching Narrative Text Reading Comprehension through KWL Strategy to Deaf Students (Universitas Negeri Semarang, 2021)
This study aimed at investigating the teacher’s verbal and non-verbal language during the reading comprehension class. This study was carried out at the special school SMPLB-B YPTB Malang. The sample was eight-graders of hearing impaired students in the academic year of 2021/2022. This study employed mix method design to collect, interpret, and analyze the data. The data was collected through interview, pre-test and post-test, observation sheet, and field note. From the result of this study, it could be seen that the teacher employed verbal language for some purposes during the reading class, they are question, invitation, direction, inform, prompt, encouragement, criticizing, acknowledgement, and comment. And she also used some non-verbal cues like gestures, facial expression, eye contact, distance, haptics, and sign language. And it also could be seen that the KWL reading strategy had been proven to be effective to improve the deaf students’ reading comprehension ability. The mean score of the pre-test was 61,5 and the mean score of the pre-test was 81. It showed that the deaf students’ reading scores increased by 19,5 points after being taught using the KWL strategy. This strategy also triggered a positive and profound effect on the deaf students’ mood which boosted students’ participation, motivation, and interest. This research was expected to give a contribution to English teaching learning in special schools..